Gender based violence and HIV AIDS in South Africa a bibliography - Fox, Susan; Nkosi, Zinhle; Kistner, Ulrike (Centre for AIDS Development, Research and Evaluation, 2003)
A companion document to a series of reviews of gender-based violence and HIV/AIDS in South Africa available on the CADRE website.
Keywords: Frau; Gesellschaft; AIDS (Disease) -- Social aspects -- South Africa -- Bibliography; Child abuse -- South Africa -- Bibliography; HIV infections -- Social aspects -- South Africa -- Bibliography; Women -- Violence against -- South Africa -- Bibliography; Südafrika (Staat); Bibliografie